Menavigasi Relevansi Pendidikan IPS Di Era Disrupsi - Fadli Marsendi; Ghina Shabina Luthfiyah; Nabila Dwi Andriani; Ritsalisa Aufi; Istiqomah Putri Lushinta (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
This article discusses the importance of Social Sciences (IPS) education in facing the challenges that continue to grow in the era of globalization and disruption. Social studies education has an important role in preparing students to become knowledgeable citizens and able to think critically. However, in this era of disruption, social studies education is faced with various challenges, including adapting the curriculum to the needs of an increasingly complex and dynamic era. This article uses a qualitative approach in its research through literature study techniques, researchers analyze the relevance of social studies education in the era of disruption. The results of this research provide an indepth understanding of how social studies education can be adapted and strengthened amidst ongoing global issues. By adapting the curriculum and appropriate teaching methods, social studies education can prepare the younger generation to face and be part of the solution in overcoming existing challenges wisely. This article also identifies factors that influence the success of adapting social studies education to face existing challenges. Thus, this article makes an important contribution in navigating issues of the relevance of Social Sciences Education in an era of disruption, as well as providing comprehensive insight and understanding of this topic.